Pengaruh Pembelajaran Praktikum Sederhana Terhadap Minat dan Motivasi Belajar IPA Peserta Didik Kelas IV MI Muhammadiyah Nunu - Nurfadillah, Nurfadillah; Arda, Arda; Ardiansyah, Ardiansyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research was motivated by the condition of students in class IV MI Muhammadiyah Nunu who during the learning process did not pay enough attention to explanations from educators. This occurs due to a lack of interesting activities in learning, resulting in a lack of interest and motivation to learn in students. The sample for this research was 19 class IV students at MI Muahammadiyah Nunu. This study uses a quantitative approach. Data collection techniques through observation, questionnaires, interviews and documentation. The data analysis techniques used are validity testing, reliability testing, normality testing and hypothesis testing. Hypothesis testing using the Paired Sample T-Test obtained a significance value for interest in learning of 0.748, this value is greater than 0.05, so it is assumed that Ha is rejected and H0 is accepted, which means there is no influence of simple practical learning on interest in learning science in class IV MI Muhammadiyah students. Nunu. Meanwhile, the results of the learning motivation hypothesis test obtained a significance value of 0.045, this value is smaller than 0.05, so it is assumed that Ha is accepted and H0 is rejected, which means that there is an influence of simple practical learning on the science learning motivation of class IV students at MI Muhammadiyah Nunu.